3 months transit time to Mars for human missions using SpaceX Starship - Jack Kingdon (Scientific Reports)
Abstract Historically, spacecraft have followed trajectories that took between six and nine months to reach Mars, using traditional chemical propulsion on roughly Hohmann transfers. It is commonly believed that advances in propulsion technology, such as nuclear thermal or VASIMR, are necessary to reduce that transit time. In this paper, we show the feasibility of transit to Mars using the SpaceX Starship taking 90 days. We outline two trajectories that reduce each transit to between 90 and 104 days each way. These trajectories are within NASA career radiation limits, while 180-day trajectories are not.